Dampak Modernitas Terhadap Identitas Sosial Makanan Tradisional Surabaya ‘Rujak Cingur’ - Petrus Paulo Mulawato; Pambudi Handoyo (Universitas Lambung Mangkurat, 2024)
Modernity that exists in every Indonesian can bring changes in various aspects of life, ranging from the economy, education, lifestyle, to culture such as food. Traditional food is a culinary culture with a distinctive flavor that can be accepted by the tongue of a community in a particular area. Culinary specialties in Surabaya as the capital of East Java province have been widely recognized by the people of Indonesia, one of which is rujak cingur. Assisted by Henri Tajfel and Erving Goffman's social identity theory, the author analyzed the theory on rujak cingur. In this research, the author uses qualitative methods to obtain data that is in accordance with the phenomena that occur. Modernization is inevitable in the current technological era, especially in Indonesia which is starting to lead to the era of society 5.0. However, we must be able to minimize any negative effects encountered when passing through this era. All efforts to maintain traditional cultures must be increased, starting from studying local cultures thoroughly, spreading and teaching them to the public, especially young children